Mobile Application Development Training in Mobile Software Ecosystem: Investigating the Developer eXperience - Fontão, Awdren de Lima; Bonifácio, Bruno A.; dos Santos, Rodrigo Pereira; Dias-Neto, Arilo Claúdio (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2018: Anais do XVII Simpósio Brasileiro de Qualidade de Software, 2018)
In a Mobile Software Ecosystem (MSECO), large software organizations (or keystones) need to attract/coach external developers to meet users' demands. In this scenario, it is necessary to evaluate developers' experiences during their involvement in trainings as a strategy to engage developers to contribute to the MSECO expansion (quantitatively and qualitatively). In this paper, we report a study on the comparison of a process-based approach for training mobile application developers in MSECO against an ad hoc approach (developer's and evangelist's personal processes) to analyze the effect of evangelist-developers interaction in MSECO from Developer experience (DX). We also propose a set of steps to assist keystone organizations to govern developers based on DX sources and with evangelists' support in trainings.